Perbandingan Efektivitas Metode Pembelajaran Praktikum, Video Digital, dan Konvensional dalam Pembelajaran Perubahan Fisika dan Kimia di SMPN 3 Cikancung - Fikri Andi Asri; Euis Rizkika Rauf; Melvin Aldila (Al-Alam: Islamic Science Education Journal, 2026)
Science plays a crucial role in developing students’ critical thinking and conceptual understanding of natural phenomena. However, science learning in schools is still dominated by teacher-centered conventional methods, resulting in low learning outcomes and limited scientific skills. This study aims to compare the effectiveness of three learning methods, practical experiments, digital video, and conventional instruction, on students’ learning outcomes in the topic of physical and chemical changes at SMP Negeri 3 Cikancung. This research employed a quasi-experimental method with a pretest-posttest non-equivalent control group design. The sample consisted of three classes selected purposively, each representing practical, digital video, and conventional learning groups. The research instrument was a validated and reliable learning achievement test. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney post hoc test. The results indicated a significant difference among the three learning methods with a significance value of 0.007. Further analysis revealed significant differences between the practical and conventional groups (p = 0.005) and between the practical and digital video groups (p = 0.009), while the digital video and conventional groups showed no significant difference (p = 0.468). It can be concluded that the practical learning method is the most effective in improving students’ learning outcomes, whereas digital video media serves as a useful complementary alternative when laboratory facilities are limited.